The Jews: a contrary people - Bauʾer, Yehudah (Lit-Verl., 2014)
To start from the end -- A contrary people -- Holocaust, God, and religion -- Jews and non-Jews--sympathy, indifference, and antisemitism : the West and Christian civilization -- Antisemitism in the Moslem world -- Genocide -- Re-thinking the Holocaust -- Back to the present : Jewish identity, secularism, Zionism, and a place in the world